Effect of dietary suppelentation of vitamin-c and spirulina (Arthrospira platensis) on growth performance and haematological parameters of rohu, Labeo rohita (hamilton, 1822) - Ranjana Damle; Manoj Singh; Dushyant Kumar Damle; Jham Lal (The Bioscan, 2024)
An experiment was conducted for 60 days to evaluate the growth performance, feed utilization and haematological parameters of rohu, Labeo rohita, under different dietary treatments.